The Multimodal Image Evolution in Video Games - Lekszycka, Mariola (Replay. The Polish Journal of Game Studies, 2019)
The article is an attempt to respond to the question whether a digital game can be considered as an image. The theoretical basis for defining the category of image is the research of Jan Białostocki, Georges Didi-Huberman and Hans Belting. Due to the multimedia nature of video games, author decided to use the multimodal method to study the imaging potential of games. On the basis of three titles (Pong, Tomb Raider and The Witcher 3: Wild Hunt), author carried out an analysis and observation of the evolution of individual elements (modes) that make up the whole digital game. The results of the research determine the evolution of the imagery potential in the history of games, the change of the player’s role and influence on productions, but also significantly contribute to in-depth reflection on games as artifacts of contemporary culture.